Optimizing model for agile product development in garment industry - Suhartini Suhartini; Mokh Suef; Udisubakti Ciptomulyono; Erwin Widodo (Journal of Industrial Engineering and Management)
Purpose: This research aims to determine an optimal plan for product development process. The developed product is a sustainable product with an agile concept. Mathematical models are involved to determine the optimal value of the number of product ideas and it is profits. The mathematical model will be of beneficial to create product development process strategies.